2022
DOI: 10.1002/adfm.202204149
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Computational–Experimental Hierarchical Approach for the Rational Design of an IL/UiO‐66 Composite Offering Infinite CO2 Selectivity

Abstract: Owing to the possibility of generating theoretically unlimited numbers of ionic liquid (IL)-metal-organic framework (MOF) combinations, experimental studies on IL/MOF composites for gas separation applications are mostly conducted on a trial-and-error basis. To address this problem, an integrated computational-experimental hierarchical approach is presented for selecting the best IL-MOF combination for a target gas separation application. For this purpose, UiO-66 and pyrrolidinium-based ILs are chosen as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The catalytic behavior of the sample was investigated. Also, a literature method was followed for the preparation of UiO-66 and UiO-66-NH 2 crystals. The same method was used for UiO-66 and UiO-66-NH 2 , but it did not lead to the creation of a thin film of MOF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic behavior of the sample was investigated. Also, a literature method was followed for the preparation of UiO-66 and UiO-66-NH 2 crystals. The same method was used for UiO-66 and UiO-66-NH 2 , but it did not lead to the creation of a thin film of MOF.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most significant batches of porous materials is metal–organic frameworks (MOFs). Owing to a large surface area, adjustable attributes, and peerless topology, MOFs are extremely advantageous in gas adsorption, , catalysts, and other usages . The postsynthetic modification (PSM) of MOFs is an appropriate way of synthesizing functionalized MOFs and begetting numerous active positions. , Postimmobilized metal ions or metal nanoparticles thereon on a MOF scaffolding is a very powerful instrumentation for inorganic catalysts that merges the preponderances of simple separation and restoration of heterogeneous catalysts with the great catalytic activity of dissolved transition-metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The band at 742 cm À1 is assigned to the asymmetric Zr-O mode stretching frequencies, whereas the two intense peaks at 1393 and 1587 cm À1 belong to the symmetric and asymmetric (O-C-O) stretching vibrations of the carboxylate group, respectively. 39 However, compared with the pristine UiO-66, blue shifts in band positions were noticed, which can be explained by the strong interaction of the O atom of [Ac] À with the metal nodes of UiO-66. 40 For instance, the peaks at 742, 1393, and 1587 cm À1 were blue-shifted to 768, 1418, and 1597 cm À1 upon the incorporation of [Emim][Ac] (Fig.…”
Section: Microstructure Of [Emim][ac]@uio-66mentioning
confidence: 98%
“…The N 2 adsorption−desorption isotherm of the [BMIM][BF 4 ]/UiO-66 composite (Figure S8) showed a reduction in both the surface area and pore volume (Table S5) compared to that of pristine UiO-66, indicating the successful incorporation of IL molecules into the MOF pores, consistent with the studies of previously reported IL/MOF composites. 6,9,59 Moreover, conductor-like screening model for realistic solvents (COSMO-RS) solubility calculations (Figure S9) demonstrated that N 2 has almost negligible solubility in [BMIM][BF 4 ] at the BET measurement conditions.…”
Section: Synthesis Characterization and Adsorption Measurements Of [B...mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), consisting of metal nodes and organic linkers, have been widely studied for gas separation thanks to their tunable pore sizes and chemical functionalities. One of the major advancements in this field is the incorporation of ionic liquids (ILs) into MOFs via post-synthesis modification techniques , to improve the selectivity of MOFs by tuning the relative affinity of composites for a specific molecule, such as CO 2 . Experimental studies have examined a very limited number of IL/MOF composites to date for CO 2 /N 2 , CO 2 /CH 4 , , , and CH 4 /N 2 ,,, separations and revealed their high gas separation potentials. There may be many other IL/MOF composites that can outperform the existing porous materials in terms of gas separation performance.…”
Section: Introductionmentioning
confidence: 99%